Strategi Penataan Pedestrian Way Berbasis Global Walkability Index Untuk Mencapai Liveable Street Corridor Jalan Ahmad Yani Kabupaten Jember - Muhammad Sufyan Rendi Wirawan (Fakultas Teknik, 2026)
Urban development in Jember Regency has increased the demand for pedestrian facilities that are safe, comfortable, and capable of supporting community mobility. Ahmad Yani Street, located within the Golden Triangle area of Jember, functions as a corridor dominated by commercial, office, and public service activities, resulting in high pedestrian movement. However, the existing pedestrian facilities still experience several problems, including inadequate infrastructure, limited comfort, and suboptimal pedestrian environments. This study aims to analyze pedestrian satisfaction and comfort based on the indicators of the Global Walkability Index (GWI) and Liveable Street, identify the lowest-scoring indicators in each corridor segment, and develop revitalization recommendations based on the concept of a pedestrian-oriented corridor. A quantitative approach was employed using questionnaires distributed to 100 respondents through accidental sampling. The study area was divided into three segments according to land-use characteristics to obtain more specific analys es. The research instrument was tested using validity and reliability analyses, while data were analyzed using the Customer Satisfaction Index (CSI) and Mean Satisfaction Score (MSS). The results indicate that all corridor segments fall within the moderately satisfied category, with CSI values of 63.82% for Segment 1, 61.89% for Segment 2, and 62.00% for Segment 3. Indicators with the lowest satisfaction scores were identified as priorities for revitalization. The proposed design emphasizes improving pedestrian facilities through the implementation of a pedestrian-oriented corridor while maintaining Ahmad Yani Street's primary function as an urban collector road.
Validasi dan Finalisasi Ratna 4 Agustus 2026
Keywords: Pedestrian Way; Global Walkability Index; Liveable Street; Customer Satisfaction Index